Analisis Perjanjian Sewa Menyewa Antara Pelaku Usaha Penyewa Kamera DSLR Dan Tindakan Konsumen Yang Beritikad Tidak Baik Di Era Ekonomi Digital - Nimas Parawansyah Pramadhyta Galuh Muktasyim; Putri Handayani (JOURNAL SAINS STUDENT RESEARCH, 2023)
A rental agreement is a form of agreement that is widely used in everyday life, including in camera rental business activities. In the era of the digital economy, camera rental agreements are increasingly being used, both by businesses and consumers. However, in this era there is also the potential for bad consumer actions in implementing camera rental agreements. Consumer actions that are not good in implementing the camera rental agreement can be in the form of default, namely not fulfilling their obligations in accordance with the agreement. Defaults can include delays in returning the camera, damage to the camera, or even loss of the camera. Bad consumer actions in implementing camera rental agreements can be detrimental to business actors. Therefore, business actors need to take legal protection measures to anticipate these losses. Efforts for legal protection that can be taken by business actors include: Drawing up a clear and detailed rental agreement, and containing strict provisions regarding obligations and sanctions for consumers who default. Carry out identity and guarantee checks from consumers before renting out cameras. Supervise the use of cameras by consumers. Carry out complete documentation about the condition of the camera before and after renting it.